Employing immigrant women from Albania and Ukraine in domestic services in Greece. - Sakellis, Ioannis; Spyropoulou, Natalia (The Greek Review of Social Research, 2007)
<div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 361.912px; transform: rotate(0deg) scale(1.10984, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="423.96">The mass influx of both male and female immigrants in Greece has been the core <div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 379.525px; transform: rotate(0deg) scale(1.03397, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="424.2732">characteristic of Greece’s economic growth for the last two decades. All available data <div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 397.139px; transform: rotate(0deg) scale(1.02494, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="424.32360000000006">lead us to the conclusion that immigration to Greece is motivated by economic factors: <div style="font-size: 12.2681px; font-family: serif; left: 101.623px; top: 414.739px; transform: rotate(0deg) scale(1.11189, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="424.7424">the pursuit of employment. In this article we shall attempt to place the work of <div style="font-size: 12.2681px; font-family: serif; left: 101.623px; top: 432.353px; transform: rotate(0deg) scale(1.12189, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="424.0752">immigrant women in the context of the hierarchical and exploitive relations that <div style="font-size: 12.2681px; font-family: serif; left: 101.623px; top: 449.967px; transform: rotate(0deg) scale(1.02952, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="138.98520000000002">prevail in the labour market. <div style="font-size: 12.2681px; font-family: serif; left: 120.516px; top: 467.58px; transform: rotate(0deg) scale(1.01342, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="405.3672">The article consists of three parts. The first part describes the hierarchical structure <div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 485.194px; transform: rotate(0deg) scale(1.02497, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="424.33799999999997">of the Greek labour market and outlines the upcoming developments and the emphasis <div style="font-size: 12.2681px; font-family: serif; left: 101.621px; top: 502.794px; transform: rotate(0deg) scale(1.03255, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="424.3788000000002">placed on gender discrimination. In the second part, the basic findings of the empirical <div style="font-size: 12.2681px; font-family: serif; left: 101.622px; top: 520.408px; transform: rotate(0deg) scale(1.00708, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_143_0" data-canvas-width="323.2715999999999">research are presented. The third part draws the main conclusions.